2005
DOI: 10.1007/s00330-005-2863-1
|View full text |Cite
|
Sign up to set email alerts
|

Higher lesion conspicuity for SENSE dynamic MRI in detecting hypervascular hepatocellular carcinoma: analysis through the measurements of liver SNR and lesion–liver CNR comparison with conventional dynamic MRI

Abstract: The aim of our study was to compare the signal-to-noise ratio (SNR) of liver parenchyma and the contrast-to-noise ratio (CNR) of hypervascular hepatocellular carcinoma (HCC) between conventional and SENSE dynamic MRI. Thirty-one consecutive patients who were strongly suspected of having HCC were enrolled in our study. The subjects consisted of 20 men and 11 women aged 52 years to 79 years (mean 66.8 years). Dynamic MRI was performed for each patient, with SENSE (SENSE MRI) and without SENSE (conventional MRI) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…These fine intranodular changes in arterial supply, although better demonstrated by CTAP and CTHA, can also be demonstrated by noninvasive methods, such as dynamic CT, dynamic MRI, Doppler or contrast-enhanced US (Figs. 13, 14) [5,9,62,63]. However, the slight changes in portal supply cannot be accurately evaluated by noninvasive techniques-a possible exemption might be contrast-enhanced US [63,64]-therefore, CTAP may be necessary for evaluation.…”
Section: Groups II and Iii Nodules Had Intermediate Attenuation Levelsmentioning
confidence: 96%
“…These fine intranodular changes in arterial supply, although better demonstrated by CTAP and CTHA, can also be demonstrated by noninvasive methods, such as dynamic CT, dynamic MRI, Doppler or contrast-enhanced US (Figs. 13, 14) [5,9,62,63]. However, the slight changes in portal supply cannot be accurately evaluated by noninvasive techniques-a possible exemption might be contrast-enhanced US [63,64]-therefore, CTAP may be necessary for evaluation.…”
Section: Groups II and Iii Nodules Had Intermediate Attenuation Levelsmentioning
confidence: 96%
“…One previous report assessed quantitative evaluation of SENSE dynamic MRI of the liver [20], in which liver SNR with SENSE was decreased compared to without SENSE. In contrast, our quantitative evaluation showed that the liver SNR with SENSE was higher than without SENSE, in spite of the theoretical reduction in SNR.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, to evaluate the FLL conspicuity, all 40 FLLs in 27 of the 70 patients were included: 21 HCCs (1.7 ± 1.3 cm; range, 0.6–2.5 cm); 17 metastases (1.1 ± 1.0 cm; range, 0.2–4.5 cm); and two hemangiomas (3.2 ± 0.5 cm; range, 2.7–3.7 cm). The two readers independently scored each image set for lesion conspicuity using a five-point scale that higher scores indicate better conspicuity (score 1, not delineated; score 5, clear depiction of FLLs with sharp margin and clear contrast to the liver parenchyma) (25). The image number, liver segmental locations of the tumors and the maximal size were also recorded.…”
Section: Methodsmentioning
confidence: 99%